The influence of stress on children’s speech in the context of war - Skrypnyk, Antonina; Labenko, Olha (East European Journal of Psycholinguistics, 2022)
War is an unbearable and unforeseen burden on the human psyche. Threat to existence, fear for life, loss of loved ones lead to an increase of non-psychotic borderline disorders, including post-traumatic stress disorder. Children represent the most unprotected and vulnerable part of the population. Being in the zone of military conflict, they acquire a tragic experience that deforms their consciousness, their values and outlook. Children experience mood swings, depression, unmotivated aggression, obsessive states, overwhelming fear and anticipation of retelling the experienced events. The article is devoted to the analysis of speech characteristics of children who witnessed the Russo-Ukrainian war, which began on February 24, 2022. The study focuses on the description of the verbalization of the psychological state of a child who witnessed bombings and shelling, children from the occupied territories who had to leave their homes, and children who, not being direct witnesses of military operations, have been forced to live in temporary refugee camps for six months unable to return to their houses. The authors analyze ways of verbalizing fear, anxiety, obsessive states, types of verbal aggression. The article deals also with the influence of parents on overcoming or, vice versa, increasing children's stress.Disclosure Statement No potential conflict of interest was reported by the authors.